Increasing the Productivity of Public Health Awareness Through Quality Education - Choirudin; Arief, Hanief; Athar Ismail Muzakir, Muhammad; Radiwan; Kaliwanto, Budi; Karnadi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The purpose of this article is to understand the importance of improving health awareness through education to achieve a quality and productive society. This article presents a synthesis of various scientific studies examining the impact of health education on increasing health awareness and its implications for society. The research methods used included a descriptive qualitative approach, a literature review, and a document analysis. The results show that health education has a positive impact on behavior change towards a healthy lifestyle, decreased disease burden and health care costs, and improved quality of life and productivity. Challenges in implementing health education in schools were also discussed, along with effective strategies to overcome these challenges. The implications of the findings include the need for educational policies and practices that prioritize health education, integrate it into the curriculum, and provide adequate resources and support for teachers. In addition, the article recommends further research and action, including the evaluation of specific health education interventions, exploration of cultural and contextual factors, and collaboration between stakeholders, to support evidence-based health education initiatives. Overall, improving health awareness through education plays an important role in building a quality and productive society.